ANALISIS YURIDIS TERHADAP KEWAJIBAN PERS DALAM KONFLIK BERSENJATA INTERNASIONAL (STUDI KASUS KETIDAKOBJEKTIFAN LIPUTAN DALAM KONFLIK ISRAEL-PALESTINA) - Dewa Ayu Diah Ambarawati A.P (Jurnal Komunikasi Hukum, 2025)
This study has two main objectives, which are: 1) analysing, from a legal perspective, particularly in terms of international law, the fulfilment of the media's obligations in the field in covering international armed conflicts; and 2) reviewing existing regulations, both globally and locally, in order to evaluate the media's accountability as actors for the lack of objectivity in reporting, particularly in coverage of the Israeli-Palestinian conflict. Thus, it provides solutions and can be used as a basis for consideration in improving legal mechanisms against media violations that have negative impacts on several parties. To achieve these objectives, this study applies a normative legal research methodology using several approaches, namely: a legislative approach, a case approach, and a historical approach. The legal materials used as the basis for analysis and research include primary, secondary, and tertiary sources. After conducting the analysis, the research findings indicate that there has indeed been a lack of objectivity by the media, so that individuals and groups of journalists have an urgent need to maintain consistency in fulfilling their obligations to present information objectively, based on facts on the ground in accordance with journalistic principles, and not contrary to international legal norms. The lack of objectivity in the coverage of the Israeli-Palestinian conflict is influenced by indications of bias influenced by political, economic, and national interests of each media outlet. The irresponsible attitude of the press in reporting, which even causes harm, still lacks legal resolution. Therefore, the media, as an independent institution, must consistently conduct oversight, take preventive measures, and collaborate with various parties to uphold these ideals.